The use of AI in classroom-based college writing courses: A case experience - Pizarro-Romero, Javier (2025)
Artificial intelligence (AI) is making inroads into academia, transforming the dynamics of higher education. This study aims to describe the integration of AI in college writing and research in the classroom. To this end, a case study was proposed where the use of AI tools was implemented in expository and argumentative writing courses, and a qualitative methodology was adopted to detail the planning and implementation phases. The results, obtained from a questionnaire applied to students at a particular Peruvian university, reveal positive perceptions towards the assistance of AI in improving their writing skills. The paper concludes that the incorporation of AI in university academic writing courses is feasible and beneficial for the development of communicative competencies.